Impacts of Aquaculture and Domestic Wastewater on the Water Quality of Santubong River, Malaysia - Ling, Teck Yee; C.M., Michelle; L., Nyanti; Norhadi, I.; Justin, J.J.E. (David Publishing, 2010)
Developments along the Santubong River basin may have an impact on the aquatic ecosystem. To determine the impacts of activities on the water quality, ten stations were selected for water quality study over 9 months. Results show that salinity increases from 14.0 PSU upstream to 30.4 PSU downstream. Lowest DO range was 2.3-4.1 mg/L. TSS ranged was 20-13 5 mg/L and the highest was observed near construction and residential areas, the second and third highest near shrimp culture discharge areas. BODs was the highest near construction and residential areas. BODs ofa station near shrimp culture was not significantly different from the residential areas. Two stations near shrimp culture site also recorded the highest Chi-a. The highest ammonia-nitrogen, nitrite-nitrogen and reactive phosphorus were observed at stations near shrimp farm sites whereas nitrate-nitrogen was the highest near construction and residential areas. Cage culture site showed the highest phosphorus and second highest nitrite-nitrogen and ammonia-nitrogen. This study showed that TSS and BODs were elevated near residential and construction areas and nutrients were elevated near shrimp farm sites resulting in algal bloom. Therefore, it is recommended that residential and shrimp farm discharge be treated to acceptable quality before discharge to protect the aquatic resources.